Estudo das potencialidades do fruto do Ouricuri - Santos, Luana Tássia Souza dos (2015)
The ouricuri (Syagrus coronata) features high oil content, is a rustic tree, resilient, adaptable and persistent. From these features it is possible that she is a promising raw material for biofuel production, through the use of its oil for biodiesel production and enzyme Peel by fermentation for production of second-generation ethanol. This paper proposes the study of drying of the almonds of ouricuri in balance three drying temperatures (100, 80 and 60° C) for the purpose of analyzing the behavior of water loss in these temperatures and study the processes of oil extraction. Mechanical extractions were carried out (in hydraulic press and electric press) and solvent. On mechanical extraction by hydraulic press, used the following pressures: 165; 247.5; 330; 412.5 and 495 kgf/cm ². The extraction with a 495 pressure kgf/cm ² in volume showed the highest amount of oil extracted, with 52 ml 100 g of almond oil. In mechanics, for electric press, were used the following pressures: 165; 247.5 and 330 kgf/cm ². The extraction with a 247.5 pressure kgf/cm ² was the best in terms of efficiency, reaching 75% approximate. In solvent extraction variables were evaluated: time (4:00 and 2); average diameter (1.015 mm and 1.435 mm); and the solvent (hexane and ethanol), analysed statistically observed the influence of these variables. The time was determination on income, because in 2:00 had already been taken from virtually the whole almond oil. The average diameter of 1.015 mm provided an almond 1.57% increase on the amount of oil extracted with solvent ethanol 1.435 mm income higher than that presented in hexane 4.42%. From these results it was possible to develop a model of solvent extraction process in light of the significant variables. The oil extracted was characterized according to the humidity, density, pH and acidity index. The oil density performed over the limit allowed by the ANP. The bark and ouricuri fiber went through the acid and hydrothermal pretreatment, where were characterized according to pH, residual sugars total (ART),° Brix, acidity and moisture. The value of fiber ART indicated the possibility of being subject to subsequent steps of enzymatic hydrolysis and fermentation for obtaining second-generation ethanol.